1992
DOI: 10.1038/bjc.1992.87
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological evidence for a common mechanism for neuroblastoma and differentiated thyroid tumour

Abstract: Summan-Because genetic predisposition probably plays an important role in the aetiology of most of childhood cancers. studies of second primaries occurring after these cancers may be particularly informative about possible common genetic mechanisms in both of these cancers. We have studied the incidence of thyroid tumours occumng after cancer in childhood in a cohort of 592 children treated before 1970. Among these children. six later developed a thyroid carcinoma, and 18 developed a thyroid adenoma. Radiation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 13 publications
(3 reference statements)
1
16
0
Order By: Relevance
“…Second malignancies after neuroblastoma described up to now were malignant tumors of the parotid [14], kidney cell carcinoma [15], osteogenic sarcoma [16], carcinoma and adenoma of the thyroid gland [17], acute lymphoblastic leukemia [8], and myelodysplastic syndrome and its transition to acute myelogenous leukemia [18].…”
Section: Discussionmentioning
confidence: 99%
“…Second malignancies after neuroblastoma described up to now were malignant tumors of the parotid [14], kidney cell carcinoma [15], osteogenic sarcoma [16], carcinoma and adenoma of the thyroid gland [17], acute lymphoblastic leukemia [8], and myelodysplastic syndrome and its transition to acute myelogenous leukemia [18].…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study by the same group of investigators, non-palpable thyroid nodules (most being benign nodules <1 cm in size) were found in 9/16 (56%) survivors, including 2 cases of PTC [54]. Although there may be elevated thyroid cancer risk in neuroblastoma due to cancer therapy, common genetic factors and mechanisms of tumorigenesis between these 2 malignancies may also play a role [98, 99]. …”
Section: Radiation-induced Thyroid Diseasementioning
confidence: 99%
“…13,14 Furthermore, thyroid tissue in children appears to be more radiosensitive than in adults, [15][16][17] and children with neuroblastoma may even be more susceptible to radiation effects on this gland compared with children who have other malignancies. 18 To protect the thyroid against these adverse radiation effects, it is common practice to administer excessive amounts of potassium iodide during exposure to radioiodide. For instance, in nuclear accidents, such a radiation protection is advised for both adults and children.…”
mentioning
confidence: 99%